PENGARUH METODE DEMONSTRASI TERHADAP HASIL BELAJAR TEKNOLOGI DASAR OTOMOTIF (TDO) SISWA KELAS X TKR DI SMK MUHAMMADIYAH 3 KLATEN UTARA TAHUN AJARAN 2020/2021 - Adena Wury Satria Ashari; Slamet Priyanto; Samsul Hadi (JURNAL VOKASI DEWANTARA (JVD), 2023)
The Effect Of The Demonstration Method On The Learning Outcomes Of Basic Automotive Technology (TDO) Students Of Class X TKR At Smk Muhammadiyah 3 Klaten Utara Academic Year 2020/2021. Essay. Mechanical Engineering Vocational Education, Faculty of Teacher Training and Education, Sarjanawiyata University Tamansiswa Yogyakarta. This study has a purpose, to describe the effect of the demonstration method on student learning outcomes in the subject of Basic Automotive Engineering class X majoring in TKR at SMK Muhammadiyah 3 Klaten Utara. This research is a quasi-experimental research (Quasi Experiment). The subjects of this study were 25 students in class X TKR 1 as the experimental class with the Demonstration method and 25 students in class X TKR 2 as the control class with the Lecture method. The total number of class X TKR is 75 students. The research was conducted at SMK Muhammadiyah 3 Klaten Utara with data collection instruments using a multiple choice test totaling 25 multiple choices. Descriptive analysis technique, analysis prerequisite test using normality and homogeneity test, then to test the hypothesis using t-test. The results showed that by using the demonstration method in the experimental class, higher results were obtained than using the lecture method in the control class. This can be proven by testing the t-test on the post-test in the experimental and control classes which show Ha is accepted.